Emotive and metacognitive processes in post-traumatic growth of University students - Matlasevych, Oksana; Balashov, Eduard; Kotovska, Yuliia (Lesya Ukrainka Eastern European National University, 2023)
The purpose of the article was to find out the role of emotional and metacognitive processes in the post-traumatic growth of student youth. For this purpose, an online survey was conducted using the following methods: Emotion Regulation Questionnaire (ERQ), AAQ-II, Post Traumatic Growth Inventory (PTGI), The Changes in Outlook Questionnaire (CiOQ). The point-biserial correlation coefficient was used for the mathematical analysis of the data. As a result of the theoretical analysis, it was found that the prevailing theoretical models of posttraumatic growth are fundamentally cognitive. However, there are studies that have examined the relationship between PTG and metacognitive beliefs. A metacognitive way of thinking allows people to take a more critical stance on their cognitive capacities and can help facilitate PTG. It has also been found that emotivity as a linguistic embodiment of emotionality can play an important role in the development of PTG. The empirical study found that after 1 year of full-scale war in Ukraine, the average values of PTG indicators among the surveyed youth are quite high. Young people show positive changes in the perception of their own self, the emergence of new opportunities, an increase in personality strength, and a sense of inner integrity. We did not find a relationship between emotional expression and PTG. However, we did find a relationship between expression suppression and cognitive reappraisal, as well as significant relationships between cognitive reappraisal and PTG with all its components. These findings suggest that cognitive reappraisal can also be performed in relation to one's emotional reactions to traumatic events, helping young people to make sense of their traumatic experiences.
Keywords: post-traumatic growth; emotivity; metacognitive processes; suppression of expression; emotive flexibility; cognitive reappraisal; University students